Birder, she wrote - Andrews, Donna (Andrews, Donna. Meg Langslow mysteries, 2023)
"Meg is relaxing in the hammock, taste-testing Michael's latest batch of Arnold Palmers and watching the hummingbirds at their feeders when her hopes for a relaxing early summer morning are dashed. First her father recruits her to help him install a new batch of bees in the hive in her backyard. Then Mayor Shiffley recruits her to placate the NIMBYs (Not in my backyard), as she calls them - a group of newcomers to Caerphilly who have built McMansions next door to working farms and then do their best to make life miserable for the farmers. And finally Meg's grandmother, shows up, trailed by a nosy reporter who is writing a feature on her for a genteel Southern ladies' magazine. Cordelia drafts Meg to accompany her and Deacon Washington of the New Life Baptist Church - and the reporter, alas - in their search for a long-lost African-American cemetery. Unfortunately what they discover is not an ancient cemetery but a fresh corpse. Can Meg protect her grandmother - and Caerphilly - from the reporter who seems to see the worst in everything . . . and help crack the case before the killer finds another victim?"--